(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
For system frequency control, the current work proposes a multi-area power system integrating various renewable sources. An effective controller with intrinsic superior capabilities of restricting peak deviation, steady state errors, and oscillatory behavior of a dynamic system is an apparent alternative for autonomous generation control of interconnected power systems. The most difficult part of using a controller is figuring out how to get the most out of it. Because of its space complexity, the trial and error method of determining the benefit by indirect optimization with an acceptable performance index appears to be insufficient. As a result, it appears that using an effective algorithm technique to find the maximum gains for the controllers is the best option. The gains of the controllers are addressed in this work and thus are optimized using a meta-heuristic technique in this study.